A Real Time System for Traffic Monitoring By Using Kalman Filter - Abu Bakar, E.; Abdullah, A. (Journal of Engineering and Technology (JET), 2017)
Real time video vehicles’ tracking is very important in the intelligent traffic monitoring system. This is because of the monitoring system provide the useful information for the government to develop a high quality road system that can reduce and prevent accident or congestion. The challenging of development system is to detect the vehicle track and monitor the vehicle movement in real time condition. Therefore, Kalman filter is used for detecting vehicle in a different lighting condition (with and without shadow) and wireless sensor network (WSN) for transmitting real time video to the computer as an input. Then, real time video is a process via MATLAB which Kalman filter is running for detecting moving vehicle. Based on the algorithm developed, this study conducted the test on the road inside university. The results show that the algorithm can detect a moving vehicle appropriately